COVID: Orthodoxy or Conspiracy: Can the Center Hold? - Bauer, Henry (Journal of Scientific Exploration, 2022)
The conversation1 between Walach and Bobrow about The Real Anthony Fauci. Bill Gates, Big Pharma, and the Global War on Democracy and Public Health by Robert F. Kennedy, Jr., deserves to be continued. It raises quite general issues about the role of science in modern society and the influence of politics. The two questions posed by Walach are a useful framework for discussion: Is it true that we were faced with a “pandemic”? Can we really trust our institutions? A large factor in the contemporary dilemmas about COVID is that disagreeing groups offer their various dogmatic answers that are seemingly influenced more by guesswork and political attitudes than by facts of the matter. The reality is that currently available data are not sufficiently complete or reliable to answer the first question. As Walach points out, the magnitude of the infection fatality rate (IFR) is a critical issue, and currently available data are inadequate, in particular as to the variation of IFR with age and a detailed comparison of those numbers with the corresponding numbers for other respiratory infections. Another important needed comparison with other infections is the overall excess mortality, where reliable data are again not yet available; that latter comparison is quite crucial in order to avoid distracting arguing about the basis for reporting COVID deaths, which varies by geographic region within countries as well as between countries and over time.